The sedimentary and volcanic sequence of Vestfjella, Dronning Maud Land - Hjelle, Audun; Winsnes, Thore S. (Antarctic geology and geophysics : symposium on Antarctic Geology and Solid Earth Geophysics : Oslo, 6-15 August 1970, organized by the Scientific Committee on Antarctic Rsearch and sponsored by the International Union of Geological Sciences, 1972)
An area approximately 130 km long and 10-30 km wide along the inner part of the ice shelf in westernmost Dronning Maud Land is described. The nunataks which rise to a maximum of 1,132 m consist essentially of uniform basalt flows dipping slightly towards the west. These volcanic rocks are cut by an olivine-gabbro intrusion and several dykes and sills of Jurassic dolerite. Almost horizontal Lower Permian Beacon Supergroup sediments were found at one locality, about 20 km from the main range. There is no definite evidence that the volcanic rocks are younger than the Permian sediments; however, the chemical similarity with associated Jurassic dolerites and the general resemblance to Jurassic basalts in adjacent areas suggest that the Vestfjella volcanic rocks are also Jurassic age.
Keywords: Dronning Maud Land; geofysikk; geologi; sedimentologi